In Vitro and In Situ Absorption and Metabolism of Sesquiterpenes from Petasites hybridus Extracts - Disch, Lucia; Forsch, Kristina; Siewert, Beate; Drewe, Jürgen; Fricker, Gert (Planta Medica, 2018)
Petasites hybridus extract is used in the treatment of seasonal allergic rhinitis. The aim of this study was to evaluate the active constituent petasin and its isomers isopetasin and neopetasin (petasins) in the P. hybridus extract Ze 339 for liberation, dissolution, absorption, and metabolism. The determination of pH-dependent thermodynamic solubility was performed via the shake-flask method. Petasins exhibited a low solubility that was pH independent. In vivo, the concentration of solute drugs is decreased continuously by intestinal absorption. Therefore, low solubility is not assumed to be critical for in vivo performance. Additionally, dissolution of an herbal medicinal product containing P. hybridus extract Ze 339 was assessed. Furthermore, high permeability through Caco-2 monolayers was evident. Using an in situ rat model, absorption capacity for petasins was found in all tested intestinal segments, namely, duodenum, jejunum, and ileum. Besides, high metabolism was evident both in Caco-2 monolayers and in the rat intestine. To compare intestinal and hepatic metabolism of petasins, in vitro enzyme assays using liver and intestinal cytosol and microsomes (S9 fraction) of rats and humans were performed. A significantly higher metabolic rate was found in the liver S9 fraction of both species compared with the intestinal S9 fraction.
Keywords: Asteraceae; Petasites hybridus; petasin; BCS; Caco-2; dissolution; intestinal absorption; metabolism